Pengaruh Strategi Pemasaran Terhadap Minat Masyarakat pada Produk Simpanan Idul Fitri di BMT Mitra Khazanah Palembang - Indah Maharani; Hilda Hilda; Abdullah Sahroni (Jurnal Publikasi Ilmu Manajemen, 2024)
This study was conducted using a data collection method in the form of a questionnaire distributed to 86 customers and prospective customers of BMT Mitra Khazanah Palembang. Then, a quantitative analysis was carried out on the data obtained. The quantitative analysis includes testing data instruments, descriptive statistics, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests), simple linear regression analysis, and hypothesis testing (determination coefficient (Adjusted R Square) and T test). The results of this study indicate that marketing strategies partially have a significant positive effect on public interest, with a t-count value of 5.719> t-table 1.663 and a significance of 0.000 <α = 0.05. The Adjusted R Square value is 0.272, which means that 27.2% of public interest can be explained by the independent variables in the study.